Habit of Applying Magic Words (Excuse Me, Please, Sorry and Thank You) in Supporting the Character of Early Childhood in Little Star Kindergarten - Nisa, Solikhatun; Puspitasari, Ika; Arifin, Shokhibul (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Character education in early childhood has an important role in building an independent and confident personality. This study aims to determine how the habit of applying the magic words excuse me, please, sorry and thank you in supporting the character of early childhood in TKIT Little Star Surabaya. This study uses a qualitative descriptive approach. The description is compiled based on data obtained from the field, precisely at TKIT Little Star. This study uses observation and interview techniques as data collection and the subjects of this study include class teachers and A1 students who are the application of the habit of the magic words excuse me, please, sorry and thank you. In the implementation of this habit does not always run smoothly there are challenges in the implementation but with the example and real examples from the teacher makes students see and do the habit of the magic words so that ethical manners in students are formed and support character education and cooperation of parents at home is also one of the supporters. Character when it has been formed from an early age will be carried over into adulthood.